Postpartum Ovarian Vein and Inferior Vena Cava Thrombosis - Harun Arslan; Sibel Ada; Sebahattin Çelik; Tayfur Toptaş (Case Reports in Medicine)
Postpartum ovarian vein thrombosis (POVT), which generally occurs 2–15 days postpartum, is a rare complication. It can be confused with acute appendicitis, pelvic infection, ovarian torsion, tubo-ovarian abscess, and pyelonephritis. It is associated with morbidity and mortality. Here, we present a patient with postpartum OVT and IVC diagnosed by US and CT findings. She was treated successfully with no further need for any interventional procedures.